Involving Farmers : Social Assessment in the Estonia Agriculture Project - World Bank (Washington, DC, 2012)
Countries in transition from centrally planned to market economies face several challenges when planning investments. These include a lack of information about beneficiary groups, particularly those in rural areas; and the collapse of institutions maintained by the state prior to transition. During preparation of the Estonia Agriculture Project, the government sought World Bank technical assistance to undertake a social assessment (SA) to fill information gaps and initiate a process of building new local level institutions. The SA was divided into three phases, with the overall objective of building institutional capacity at both the local and the national level. Phase I has been completed. It has enabled the government to assess farmers' commitment to rehabilitation of field drainage systems, and their willingness to form farmer-managed Land and Water Associations and to share costs and assume responsibilities for operation and maintenance. Since regaining independence in 1991, Estonia has stabilized its macroeconomic situation and moved rapidly towards a market economy. Living standards, which declined dramatically in 1992 and 1993, have begun to rise in urban areas where enterprises have been privatized and industrial production has begun to revive. However, similar results have not materialized in rural areas. Estonia has the potential to be competitive in agriculture if certain constraints are overcome. The Agriculture Project, as the first Bank-supported operation, is expected to address some of these, principally the rehabilitation of field drainage systems.